A systematic review of the effectiveness of double checking in preventing medication errors. Issue 5 (22nd April 2012) - Alsulami, Z; Conroy, S; Choonara, I
Abstract : Background: Medication errors are unfortunately a constant problem in the medication treatment process. Different interventions are available to reduce or prevent medication errors from reaching the patient. Double checking by two qualified nurses is one intervention that is implemented in many children's hospitals during the medication treatment process. Objective: To determine the existing evidence base for the effectiveness of double checking processes in reducing medication error rates in prescribing, dispensing and administration. Methods: A systematic search of studies that assessed or evaluated double checking during the medication treatment process was conducted for adults and children using the following databases: Embase, Medline, British Nursing Index & Archive, Cumulative Index to Nursing & Allied Health Literature (CINAHL) and PsycINFO. The title, abstract and full article were reviewed for relevance. Studies not related to double checking medication were excluded. Results: Only 14 studies were identified as being relevant. Three studies were quantitative. Seven studies were qualitative (questionnaire and interviews). Two studies used mixed qualitative and quantitative methods. Two studies were systematic reviews. One of the three quantitative studies reported a statistically significant reduction in the error rate from 2.98 when using two nurses for drug administration to 2.21 when drug administration was performed by a single nurse but the clinical advantages of the double checking process were stated to be uncertain.1 Another quantitative study reported that a double checking policy introduced for all dispensed medicines by pharmacy staff led to a reduction in errors from 9.8 to 6 per year.2 The third study was a simulation study comparing two checklists (old checklist vs new checklist) for an ambulatory infusion pump used in a chemotherapy unit. It found that there was no significant difference in detection of pump programming errors, but detection of errors in patient identification with the new checklist (80%) was significantly higher than with the old checklist (15%).3 Conclusion: There is insufficient evidence to confirm that double checking of medication reduces the risk of medication errors. This does not mean that double checking is ineffective but simply that its effectiveness has not yet been proven. More research is required to examine the effectiveness of the double checking process.